2016
DOI: 10.4049/jimmunol.1501588
|View full text |Cite
|
Sign up to set email alerts
|

HIV-1 Env Glycoprotein Phenotype along with Immune Activation Determines CD4 T Cell Loss in HIV Patients

Abstract: The mechanism behind the selective depletion of CD4+ cells in HIV infections remains undetermined. Although HIV selectively infects CD4+ cells, the relatively few infected cells in vivo cannot account for the extent of CD4+ T cell depletion suggesting indirect or bystander mechanisms. The role of virus replication, Env glycoprotein phenotype and immune activation (IA) in this bystander phenomenon remains controversial. Using samples derived from HIV-infected patients; we demonstrate that while IA in both CD4+ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 23 publications
(41 citation statements)
references
References 72 publications
0
41
0
Order By: Relevance
“…P rogressive depletion of CD4 T cells by pyroptosis and activation-related apoptosis is the hallmark of HIV-1 infection (1)(2)(3)(4). The loss of memory CD4 T cells and, in particular, central memory CD4 T cells (T CM cells), which are critical to ensure longlasting immune protection, occurs from the onset of infection and independently predicts disease progression (5)(6)(7)(8).…”
Section: The Persistence Of Functional Memory Cd4 T Cells Represents mentioning
confidence: 99%
“…P rogressive depletion of CD4 T cells by pyroptosis and activation-related apoptosis is the hallmark of HIV-1 infection (1)(2)(3)(4). The loss of memory CD4 T cells and, in particular, central memory CD4 T cells (T CM cells), which are critical to ensure longlasting immune protection, occurs from the onset of infection and independently predicts disease progression (5)(6)(7)(8).…”
Section: The Persistence Of Functional Memory Cd4 T Cells Represents mentioning
confidence: 99%
“…In the SIV/HIV chimeric SHIV virus infection in macaques, a correlation between apoptosis and CD4 loss is also evident [ 8 , 9 ]. Multiple studies have reported increased apoptosis in peripheral blood mononuclear cells (PBMCs) from HIV infected individuals that correlates with CD4 decline [ 10 , 11 , 12 ]. Although the involvement of apoptosis in CD4 decline in HIV infections is widely accepted, the mechanism of apoptosis induction remains debated.…”
Section: Introductionmentioning
confidence: 99%
“…In a model presented in our previous study 24 we proposed a role for the Env glycoprotein phenotype, viremia and immune activation in collectively mediating CD4 bystander apoptosis. Based on the findings from this study, inclusion of CCR5 promoter polymorphisms in this model is justified (Fig.…”
Section: Discussionmentioning
confidence: 99%